Rheological Characterization of Commercial Sweetened Condensed Milk - RAMOS, AFONSO MOTA; OLIVEIRA, ANDERSON NASCIMENTO DE; DIAS, MANOELA MACIEL S.; NEVES, ERICK ORNELLAS (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
The present study have analyzed samples of sweetened condensed milk of five brands sold in the Brazilian market regarding their rheological behavior and viscoelasticity. The products presented pseudoplastic fluid behavior, illustrated by the experimental data of shear stress versus strain rate, with adjustments made to fit the Power Law and Casson models. The effect of temperature on apparent viscosity of the products followed the Arrhenius model, with activation energy values ranging from 33.8 to 40.9 kJ mol-1. The products showed loss modulus (G’’) greater than storage modulus (G ‘), indicating a semi-liquid material behavior.